A Practical English Grammar - Thomson, A. J. | Martinet, A. V. (Estados Unidos | ESTADOS UNIDOS Oxford University, New York, 1986)
A grammar reference that is known for its clear explanations and for dealing with the topics students find most difficult. Two separate books of exercises provide practice
Sin Especificar
Keywords: Ingles libro de texto para extranjeros | Ingles gramática | Problemas ejercicios